1974
DOI: 10.1139/m74-201
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic sporulation in facultatively anaerobic species of the genus Bacillus

Abstract: Sixteen strains of 11 facultatively anaerobic species of the genus Bacillus were tested for their ability to sporulate anaerobically on common laboratory media. Reliable data depended on a method providing anaerobic conditions quickly. Bacillus macerans (one strain tested) and B. polymyxa (two out of two strains tested) sporulated anaerobically without added nitrate. But B. licheniformis (one out of two strains tested) required nitrate for "anaerobic" sporulation. Anaerobic sporulation of B. macerans and B. po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In anaerobiosis, sporulation capacity in MODS medium was lower than that in aerobiosis. The previous results showed that a low concentration of oxygen led to a lower spore production on several species of the genus Bacillus (Couchot and Maier, 1974). Other experiments reported a lower spore production of Bacillus thuringiensis, genetically close to Bacillus cereus, under O 2 limitation compared with cultures with O 2 (Avignonerossa et al, 1992;Finlay et al, 2002;Foda et al, 1985).…”
Section: Discussionmentioning
confidence: 88%
“…In anaerobiosis, sporulation capacity in MODS medium was lower than that in aerobiosis. The previous results showed that a low concentration of oxygen led to a lower spore production on several species of the genus Bacillus (Couchot and Maier, 1974). Other experiments reported a lower spore production of Bacillus thuringiensis, genetically close to Bacillus cereus, under O 2 limitation compared with cultures with O 2 (Avignonerossa et al, 1992;Finlay et al, 2002;Foda et al, 1985).…”
Section: Discussionmentioning
confidence: 88%
“…Carbon dioxide also affects sporulation by enhancing sporulation of C. botulinum [57] or inhibiting sporulation of Bacillus anthracis [58]. According to the Bacillus species, sporulation in anaerobiosis is affected by other factors, such as the presence of nitrates which inhibit sporulation of Paenibacillus polymyxa and Paenibacillus macerans (both previously named Bacillus) in anaerobiosis, while it is necessary for a particular B. licheniformis strain [59]. The oxygen concentration is perceived by HK KinA via the NAD þ /NADH ratio [60] while anaerobic conditions are sensed by KinB in B. subtilis [61] ( Fig.…”
Section: Aerationmentioning
confidence: 99%